Proceedings of the 20th Annual International Conference on Mobile Systems, Applications and Services 2022
DOI: 10.1145/3498361.3538939
|View full text |Cite
|
Sign up to set email alerts
|

HearMeOut

Abstract: In South Korea, voice phishing has been proliferating with the advent of voice phishing apps: the number of annual victims had risen to 34,527 in 2020, representing financial losses of approximately 598 million USD. However, the voice phishing functionalities that these abusive apps implement are largely understudied. To this end, we analyze 1,017 voice phishing apps and reveal new phishing functionalities: outgoing call redirection, call screen overlay, and fake call voice. We find that call redirection that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This quantitative study with an experimental design analyzed 1,017 voice phishing applications obtained from an antivirus corporation and the Financial Security Institute of South Korea. Through static and dynamic analysis, the study identified three new phishing functionalities: outbound call redirection, call screen overlay, and fake call voice [69].…”
Section: Discussionmentioning
confidence: 99%
“…This quantitative study with an experimental design analyzed 1,017 voice phishing applications obtained from an antivirus corporation and the Financial Security Institute of South Korea. Through static and dynamic analysis, the study identified three new phishing functionalities: outbound call redirection, call screen overlay, and fake call voice [69].…”
Section: Discussionmentioning
confidence: 99%